2021
DOI: 10.1088/2040-8986/ac1b7c
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-enhanced rubidium atomic magnetometer based on Faraday rotation via 795 nm stokes operator squeezed light

Abstract: With the help of Stokes operator Ŝ2 squeezed state (also called polarization squeezed state (PSS)) of 795 nm light, rubidium-87 (87Rb) atomic magnetometer based on Faraday rotation (FR) has been implemented and characterized. The PSS of Stokes operator Ŝ2 of 795 nm light has been prepared by means of coherently combining the polarization coherent state (PCS) of a linearly p-polarized bright 795 nm light beam and a linearly s-polarized squeezed vacuum state (SVS) generated by a 397.5 nm ultraviolet laser pump… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…The PSN can be suppressed by introducing the squeezed light. In previous work, our group demonstrated the improvement of sensitivity by introducing a Stokes operator polarization-squeezed light in the rubidium atomic magnetometer based on the Faraday rotation [ 32 ], and we also systematically analyzed the effect of frequency detuning on the squeezed level; we found that there was an obvious loss in the squeezed level when the probe light is resonant with rubidium atomic atoms. This indicated that the probe light with large frequency detuning was a better choice for compatibility with the polarization-squeezed light.…”
Section: Sensitivity Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PSN can be suppressed by introducing the squeezed light. In previous work, our group demonstrated the improvement of sensitivity by introducing a Stokes operator polarization-squeezed light in the rubidium atomic magnetometer based on the Faraday rotation [ 32 ], and we also systematically analyzed the effect of frequency detuning on the squeezed level; we found that there was an obvious loss in the squeezed level when the probe light is resonant with rubidium atomic atoms. This indicated that the probe light with large frequency detuning was a better choice for compatibility with the polarization-squeezed light.…”
Section: Sensitivity Analysis and Discussionmentioning
confidence: 99%
“…Additionally, the dual-beam FID rubidium atomic magnetometer with large detuning of the probe beam frequency avoided atomic resonance absorption at the detection phase, which was caused by a measurement deviation [ 42 ]. This result laid a foundation for subsequent employing Stokes operator polarization-squeezed light [ 32 ] to improve SNR, and further improve the sensitivity of the magnetometer. Compared to previous works [ 32 , 41 ], FID type rubidium atomic magnetometer more broadly and accurately measured magnetic fields, and was not limited to tracking magnetic field in real-time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where we denote operator variances by Var 𝑋 = 𝑋 2 − 𝑋 2 , have led to the fruitful discovery and implementation of "polarization squeezing," which may ultimately have applications in quantum-enhanced polarimetry and other communication tasks (Abdel-Aty et al, 2002;Agarwal and Puri, 1994;Alodjants et al, 1998;Alodzhants et al, 1995;Andersen and Buchhave, 2003;Bai et al, 2021;Barreiro et al, 2011;Beduini and Mitchell, 2013;Birrittella et al, 2021;Bowen et al, 2002;Brif and Mann, 1996;Chaudhury et al, 2007;Chirkin, 2015;Chirkin et al, 1993;Civitarese et al, 2013;Corney et al, 2008;Dong et al, 2008;Gühne and Tóth, 2009;Golubev et al, 2004;Gross, 2012;Hald et al, 1999;Han et al, 2018;He et al, 2011;Heersink et al, 2003Heersink et al, , 2005Hillery and Mlodinow, 1993;Hsu et al, 2009;Iskhakov et al, 2009;Josse et al, 2003;Karassiov, 1994;Kitagawa and Ueda, 1993;Klimov and Muñoz, 2013;Klyshko, 1997;Korolkova et al, 2002;Korolkova and Loudon, 2005;Lassen et al, 2007;Luis and Korolkova, 2006;Ma et al, 2011;Mahler et al, 2010;…”
Section: Quantum Polarizationmentioning
confidence: 99%
“…Previous experiments utilized a linearly polarized optical probe field in which the coherent vacuum in the orthogonal polarization was replaced by the squeezed vacuum. They demonstrated the improved magnetometer sensitivity for ac magnetic field in the spectral range in which squeezing was observable [21][22][23][24]. Technical 1/f noise has prevented detection of slowly varying dc magnetic fields.…”
mentioning
confidence: 99%